Repeated Autologous Bone Marrow Transfusion through Portal Vein for Treating Decompensated Liver Cirrhosis after Splenectomy - Weiwei Zhang; Mujian Teng; Baochi Liu; Qiling Liu; Xin Liu; Yanhui Si; Lei Li (Gastroenterology Research and Practice)
Objective. This study is aimed at examining the impact of repeated intraportal autologous bone marrow transfusion (ABMT) in patients with decompensated liver cirrhosis after splenectomy. Methods. A total of 25 patients with decompensated liver cirrhosis undergoing splenectomy were divided into ABMT and control groups. The portal vein was cannulated intraoperatively using Celsite Implantofix through the right gastroomental vein. Both groups were given a routine medical treatment. Then, 18 mL of autologous bone marrow was transfused through the port in the patients of the ABMT group 1 week, 1 month, and 3 months after laminectomy, while nothing was given to the control group. All patients were monitored for adverse events. Liver function tests, including serum albumin (ALB), alanine aminotransferase (ALT), total bilirubin (TB), prothrombin activity (PTA), cholinesterase (CHE), α-fetoprotein (AFP), and liver stiffness measurement (LSM), were conducted before surgery and 1, 3, and 6 months after surgery. Results. Significant improvements in ALB, ALT, and CHE levels and decreased LSM were observed in the ABMT group compared with those in the control group (P<0.05). TB and PTA improved in both groups but with no significant differences between the groups. No significant changes were observed in AFP in the control group, but it decreased in the ABMT group. No major adverse effects were noted during the follow-up period in the patients of either group. Conclusions. Repeated intraportal ABMT was clinically safe, and liver function of patients significantly improved. Therefore, this therapy has the potential to treat patients with decompensated liver cirrhosis after splenectomy. This trial was registered with the identification number of ChiCTR-ONC-17012592.